Numerical Simulation and Analysis of Gas-liquid Coupled Double-acting Thermoacoustic Refrigeration System - Chi Jiaxin; Xu Jingyuan; Zhang Limin; Li Ping; Luo Ercang (Zhileng xuebao)
A novel type of gas–liquid coupled double-acting traveling-wave thermoacoustic refrigeration system is proposed to solve the low efficiency of traditional thermoacoustic refrigeration with a gas resonance tube. The study optimized the size of the system structure and analyzed its performance using numerical simulation. First, the article studied the distribution of important parameters such as sound power, pressure, and volume flow amplitude of a three-stage gas-liquid coupled double-acting traveling wave thermoacoustic refrigeration system. Then, characteristic parameters such as the acoustic power and thermoacoustic conversion efficiency of the system under different levels were investigated. Finally, the cooling power of different stages and COP with pressure were compared and analyzed. The calculation results show that when the ambient temperature is 293 K, heating temperature is 400 K, cooling temperature is 270 K, and mean pressure is 1 MPa, the COP of three-stage system reaches 0.7, the cooling power is 0.78 kW, the operating frequency is 13.8 Hz, and the relative Carnot efficiency of the system is 22.3%. As the number of system stages increases, the power density of the system increases. When the mean pressure is 10 MPa, the cooling power of the six-stage system reaches a maximum value of 16.1 kW, and the COP is 0.38.